Preparatory versus main competitions: differences in performances, lactate responses and pre-competition plasma cortisol concentrations in elite male swimmers - Bonifazi, M.; Sardella, F.; Lupo, C. (European Journal of Applied Physiology, 2000)
Two groups of elite male swimmers were studied using a similar protocol during the winter training seasons of two consecutive years. In the first season (September 1997-January 1998), eight male swimmers (age 19-25 years) of the Italian National Team participated, after 12 weeks of increased training volume, in a preparatory national competition (PWC) and then, after a further 6 weeks of specific training, in the World Championships (WC, both competitions in a 50-m pool), which represented the main competition at the end of the 18-week-long winter season. In the second season (September 1998-December 1998), a group of ten high-level male swimmers (18-22 years) participated, after 8 weeks of increased training volume, in a preparatory national competition (PIC) and then, after a further 6 weeks of specific training, in the Italian Championships (IC, both competitions in a 25-m pool), the main competition at the end of the 14-week-long winter season. A tapering period lasting 1-3 weeks was observed before the main competition in both seasons. All swimmers were competing at distances of up to 400 m; two of them participated in the study in both seasons. The swimming velocities and post-competition blood lactate concentrations were higher in the main competitions than in the preparatory competitions in both seasons. Pre-competition plasma cortisol (CORT) concentrations were higher than the initial values at the beginning of the season, reaching maximal values at the preparatory competitions and then decreasing before the main competitions in both seasons. The percentage increase in individual swimming velocity from the preparatory to the main competition was positively correlated with the corresponding increase in post-competition blood lactate (r=0.63, P=0.046) in the 1997 season (WC), and negatively correlated with the corresponding decrease in pre-competition CORT concentration (r=-0.66, P=0.019) in the 1998 season (IC). Our results indicate that a decrease in pre-competition CORT could be a prerequisite for an improvement in swimming performance.